2001
DOI: 10.1001/archpedi.155.7.831
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Use Outcomes of Adolescents Treated Clinically for Nicotine Dependence

Abstract: Adolescents utilize the medical community to seek treatment for nicotine dependence. The 6-month tobacco abstinence rate is higher than the estimates of the natural history of smoking cessation in adolescents. Medical and psychiatric diagnoses are common in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The conceptual model underlying the mFTQ was not designed as a proxy for the DSM-IV criteria. The FTQ and variants including the Fagerstrom Test for Nicotine Dependence (FTND; Heatherton et al, 1991) scale have a long history of support as valid indicators of smoking behavior and as predictors of difficulty with smoking cessation among adults (Alterman et al, 1999; Campbell et al, 1996; Patten et al, 2001; Westman et al, 1997). As a natural extension of this research, the mFTQ included a modified set of adult symptoms for adolescents to address graded levels of smoking behavior, avoidance of the physiological effects of nicotine deprivation, and perceived difficulty refraining when prevented from smoking.…”
Section: Introductionmentioning
confidence: 99%
“…The conceptual model underlying the mFTQ was not designed as a proxy for the DSM-IV criteria. The FTQ and variants including the Fagerstrom Test for Nicotine Dependence (FTND; Heatherton et al, 1991) scale have a long history of support as valid indicators of smoking behavior and as predictors of difficulty with smoking cessation among adults (Alterman et al, 1999; Campbell et al, 1996; Patten et al, 2001; Westman et al, 1997). As a natural extension of this research, the mFTQ included a modified set of adult symptoms for adolescents to address graded levels of smoking behavior, avoidance of the physiological effects of nicotine deprivation, and perceived difficulty refraining when prevented from smoking.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of studies have demonstrated the need to develop smoking cessation programs adapted to adolescents by making them attractive and tailored to the adolescents' expectations and needs (Patten et al, 2001;Vuckovic et al, 2003). However, to date, there is limited evidence from clinical trials in adolescent populations showing the efficacy of smoking cessation interventions, especially over the long term.…”
Section: Youth Smoking Cessationmentioning
confidence: 99%
“…In this regard, using alternative behavior is a useful strategy in teen tobacco cessation (Pallonen, 1998;Patten et al, 2001). Peer pressure is an important factor to take into consideration in smoking cessation interventions for teens, notably in relation to the type of group activities and group subcultures in general (Bonard et al, 2001;Moolchan et al, 2000;Patten et al, 2001).…”
Section: Youth Vernacularmentioning
confidence: 99%
“…In discussing specific populations, the 2000 PHS guideline addressed tobacco use by individuals with SUDs and by adolescents, although it did not address the two issues simultaneously (Fiore et al, 2000). Some have noted that pharmacotherapies may have adverse effects for some adolescents (Patten et al, 2001), and nicotine replacement products are not available over the counter for purchase by individuals younger than 18 years old (Moolchan, Aung, & Henningfield, 2003). However, the 2000 PHS guideline suggested that pharmacotherapies were appropriate if adolescents were nicotine dependent and wanted to cease using tobacco products (Fiore et al, 2000).…”
Section: Introductionmentioning
confidence: 99%